Structural-functional modifications of the liver to chronic radioactive exposure in pygmy wood mouse (Apodemus uralensis) within the East-Urals Radioactive Trace. (April 2019) - Orekhova, Natal´ya A.; Modorov, Makar V.; Davydova, Yulia A.
Abstract: The hepatic parameters (contents of glycogen, total lipids, nuclear and cytoplasmic proteins, DNA and RNA, fructose-6-phosphate, water, lipid peroxidation products, as well as activities of succinate dehydrogenase and glucose phosphate isomerase), radiometric data, and the relative population abundance of the pygmy wood mouse ( Apodemus uralensis Pall., 1811) inhabiting natural (Middle Urals, Southern Urals, and Trans-Urals) areas and radioactivity territory (the EURT zone after of the Kyshtym accident in the South Urals in 1957) were analysed. Structural-functional modifications of the liver in A. uralensis from the EURT area are presented, taking into account irradiation power by dose-forming radionuclides (external and internal exposure to 137 Cs and 90 Sr), population size, and reproductive status (sexually immature and sexually mature yearlings, representing different ontogenetic patterns). The sexually immature mice from the EURT area can be considered to be the more sensitive (reactive) intrapopulation group to synergistic factors, such as radiation burden and population overabundance. The extent of structural-functional hepatic modification under current conditions of radionuclide exposure, in addition to the 60 year long effect of radioactive contamination in the EURT, can exceed the level of natural (geographic) variation observed in this species in the Urals region, which points to a long term evolutionary-ecological process. Graphical abstract: Image 1 Highlights: Complex analysis of the liver in the pygmy wood mouse from the EURT and natural areas. The radiation dose rate, population abundance, and puberty showed combined exposure. Immature mice are more sensitive to the synergy of irradiation and overpopulation. The chronic radioactive action and natural stress-affects are unidirectional. The technogenic change is comparable to geographic variability of mice in the Urals.